Implementation of the Course Scheduling Model at State Vocational High School 4 Medan - Swanda, Ari; Syahputra, Dinur; Ruziq, Fahmi (Journal of Technology and Computer, 2024)
Course scheduling is one of the most common problems in education. The number of rooms, the number of teachers, the number of subjects that must be taught, and the teaching hours of teachers who teach not only one school so that a method is needed so that there is no block with other schedules. In designing a course schedule with a limited number of teachers and there are teachers who cannot teach on certain days will be a complicated problem to be solved manually. adaptive which is commonly used to solve a value search in an optimization problem. Adaptive is commonly used to solve a value search in an optimization problem. i.e. the progression of generations in a natural population slowly follows the principle of natural selection or "he who is strong, survives". By emulating this theory, it can be used to find solutions to real-world problems. By applying the course schedule design time and teachers can choose the time to teach according to their time choice so that the course schedule design can be completed faster than the course schedule design. Can be completed faster than the manual schedule design.